Enhancing the supercapacitor performance of NiCo2O4 microflowers by reduced graphene oxide nano-sheets - Saei, Worawee; Buranasiri, Prathan; Karaphun, Attaphol; Ruttanapun, Chesta; Sriwong, Chaval (My University, 2021)
This work presented the preparation and supercapacitor performance of a spinel nickel-cobalt oxide (NiCo2O4) microflowers mixed with nano-sized reduced graphene oxide (rGO) sheets. The hybrid material (NiCo2O4/rGO), pure NiCo2O4 and nano-sized rGO samples were characterized and confirmed by several techniques, such as XRD, SEM and EDS. The supercapacitive properties of all prepared samples were also studied using an electrochemical measurement technique (CV and GCD). The results revealed that the NiCo2O4/rGO (484.1 F.g-1) hybrid electrode exhibited much higher specific capacitance than those of pristine NiCo2O4 (358.3 F.g-1) and nano-sized rGO (113.8 F.g-1) electrodes, respectively. Hence, this work indicates that the supercapacitor performance of NiCo2O4 mixed rGO hybrid materials is more superior to the pure NiCo2O4 microflowers and nano-sized rGO sheets.